Effect of Dietary Factors on Induction of Fatty Liver-Hemorrhagic Syndrome and its Diagnosis Methods with Use of Serum and Liver Parameters in Laying Hens - Yousefi, M.; Shivazad, M.; Sohrabi-Haghdoost, I. (International Journal of Poultry Science, 2005)
An experiment was conducted to determine the effect of dietary factors on induction of fatty liver hemorrhagic syndrome (FLHS) and its diagnosis methods with use of selected serum enzymes on Hy-line W-36 hens. The experiment was conducted in completely randomized design with 6 treatment groups and 4 replicates each with ten hens from 94 to 106 wk of age. Three 28-d periods used for different dietary factors including:1) Control (C); 2) Low methionine (LM); 3) Low linoleic acid (LLA); 4) High energy (HE); 5) Low methionine, linoleic acid, choline and high energy (LM-LLA-LCH-HE) and 6) Low choline (LCH). Feed intake, body weight, egg production (EP), egg weight, egg quality, serum and liver parameters were measured at the end of each 28-d periods. Overall feed intake was significantly (P< 0.05) lower for the hens fed HE diets compared to the control. Overall egg weight was significantly (P< 0.05) lower for the hens fed LM and LM-LLA-LCH-HE compared to the control. Overall Liver weight was significantly (P< 0.05) higher for the hens fed LLA and LM-LLA-LCH-HE compared to the control. Liver hemorrhage score (LHS) was positively correlated (P< 0.05) with liver weight. Serum enzyme activities including: aspartate aminoteransferase (AST), alanine aminoteransferase (ALT), lactate dehydrogenase (LDH) were not significantly affected by treatment groups. Although the AST enzyme activity was not significantly different, but it was numerically higher for all dietary treatments except HE diet. The results showed the effectiveness of dietary factors on induction of FLHS in laying hens. AST enzyme activity could be used for diagnosis of FLHS in laying hens.